2023
DOI: 10.1002/anie.202315681
|View full text |Cite
|
Sign up to set email alerts
|

Direct Quantification of Nanoplastics Neurotoxicity by Single‐Vesicle Electrochemistry

Shiyi Wei,
Fei Wu,
Jing Liu
et al.

Abstract: Nanoplastics are recently recognized as neurotoxic factors for the nervous systems. However, whether and how they affect vesicle chemistry (i.e., vesicular catecholamine content and exocytosis) remains unclear. This study offers a first direct evidence on the nanoplastics‐induced neurotoxicity at a single‐cell level by single‐vesicle electrochemistry. We observe the cellular uptake secretion of polystyrene (PS) nanoplastics into model neuronal cells and mouse primary neurons, leading to cell viability loss dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Under KCl stimulation, the current first rises sharply, producing spike I within 30 s and then falls to baseline as dopamine is rapidly metabolized, and the stimulus-generated dopamine is 6.5–7.6 μM [ I (nA) = 0.16 C DA (μM) + 0.06, r = 0.9998]. Interestingly, reproducible shoulder spike II (1.0–1.2 μM) is generated during the current drop, which behaves similarly to the kinetic process of the neurotransmitter release from vesicles via exocytosis. Similarly, Zhang et al recently showed that such double spikes occurred when neighboring vesicles aggregate to form a dimer and that the distance between the vesicles correlated with the separation of the double spikes. Furthermore, they also recorded complex events in high K + -stimulated PC12 cells, such as single spikes, double spikes, and even multispikes.…”
Section: Resultsmentioning
confidence: 95%
“…Under KCl stimulation, the current first rises sharply, producing spike I within 30 s and then falls to baseline as dopamine is rapidly metabolized, and the stimulus-generated dopamine is 6.5–7.6 μM [ I (nA) = 0.16 C DA (μM) + 0.06, r = 0.9998]. Interestingly, reproducible shoulder spike II (1.0–1.2 μM) is generated during the current drop, which behaves similarly to the kinetic process of the neurotransmitter release from vesicles via exocytosis. Similarly, Zhang et al recently showed that such double spikes occurred when neighboring vesicles aggregate to form a dimer and that the distance between the vesicles correlated with the separation of the double spikes. Furthermore, they also recorded complex events in high K + -stimulated PC12 cells, such as single spikes, double spikes, and even multispikes.…”
Section: Resultsmentioning
confidence: 95%